International Collaboration in the Time of COVID-19: The World Hospice and Palliative Care Social Work Network. Issue 2 (3rd July 2021) - Oltmann, Carina; Otis-Green, S.; Blackburn, P.; Maasdorp, V.; D'Urbano, E.; Lema, D.; Thomas, P.; Roulston, A.; Firth, P.; Remke, S.
Abstract: In the context of widespread loss, isolation, and grief due to COVID-19, palliative social workers came together in the fall of 2020 to form an international group named the World Hospice and Palliative Care Social Work Network (WHPCSW). This emerging global network is committed to amplifying the innovative work, nuanced skills, research, and education and training provided by palliative social workers across different settings around the world. This article highlights some of the novel interventions developed by social workers in response to the pandemic and describes this coalescing WHPCSW network along with information about its mission and membership.